Vegetation Diversity And Carbon Storage In Agroforestry Systems In The Buffer Zone Of Way Kambas National Park - KD, Elisabeth Violetta; Trirana, Sarah; Saputri, Hanum Resti; Rahmadhani, Khorina; Hartoyo, Adisti Permatasari Putri (Journal of Tropical Silviculture, 2024)
The local community in the buffer zone of Way Kambas National Park, particularly in Labuan Ratu VII Village, relies primarily on farming as their main livelihood by implementing an agroforestry system. Agroforestry systems have the potential to contribute to climate change mitigation as carbon sinks, while also enhancing income through diverse plant combinations. This study aimed to explore agroforestry management and carbon stock in the buffer zone of Way Kambas National Park. The methods employed included vegetation analysis across 15 plots and interviews with local communities. The local community practices agroforestry based on traditional knowledge and local wisdom. The results indicated that the highest carbon stock was observed in plot 12 (0.023 tons/ha). The average and total carbon stock at the research site were 0.084 tons/ha and 0.124 tons/ha, respectively. The variation in carbon stock across fields depended on plant diversity, density, and agroforestry management practices. Keywords: Buffer zone, climate change, local wisdom